Teachers’ perception of collaborative instruction for students with learning disabilities in inclusive schools in Ibadan metropolis, Nigeria (2012)
This study examined the perceptions of regular and special education teachers in Ibadan, Oyo State, Nigeria on collaborative instructional practic.es in inclusive schools. The descriptive research design was adopted with a total of one hundred and fifteen randomly selected teachers comprising (102 regular teachers, [88.7%], and 13 special teachers, [11.3%]). A self-designed questionnaire tagged “Perception of Collaborative Instructional Practices for Students with Learning Disabilities in Inclusive Education Setting” (PC1PSLD) [α =0.77] was utilized. Data obtained were analyzed. Using frequency counts, percentages, means, standard deviations and t -test statistics at 0.05 level of significance. Results show ed that respondents got an over all mean of 3.15 with highest mean as 4, indicating a positive perception towards ten ingredients necessary for effective collaborative practices for students with learning disabilities in inclusive schools. Likewise, the study showed that special education teachers have positive perceptions about the characteristics of three models of collaboration namely, co-teaching (overall mean =3.21); collaborative Consulting (overall mean = 2.94); and partnership with parents (overall mean = 3.23). Besides, no significant difference was found between regular and special education teachers in their perception of collaborative instructional practices for students with learning disabilities in inclusive schools (t = 0.922; df =113). It was recommended that regular and special education teachers should be exposed to continuous professional development programmes to enable them to become more skillful in teaching students with learning disabilities. Teachers were also advised to adopt co-teaching, collaborative consultation, and partnership with parents, in their classrooms for improved students' outcomes.